The Effects and Determinants of Training. - Greenhalgh, C; Stewart, M (1987)
Using retrospective work history data for over 50,000 men and women in Great Britain surveyed in 1975-76, the authors document the amount of vocational training occurring in a ten-year period and discuss its effects and determinants. The effects of training on occupational status are estimated for married and single men and women, using a model which controls for unobserved fixed personal attributes. Women are found to receive significantly less full-time training than men but such training yields larger returns for women than for men.